2005
DOI: 10.1111/j.1552-6569.2005.tb00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Localized Cerebral Blood Flow Reductions in Patients With Heart Failure: A Study Using99mTc-HMPAO SPECT

Abstract: These preliminary findings indicate that posterior cortical areas of the brain may be particularly vulnerable to brain perfusion reductions associated with HF and suggest that functional deficits in these regions might be relevant to the pathophysiology of the cognitive impairments presented by HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…Reduced CBF in HF, as demonstrated by others (Alves et al, 2005; Gruhn et al, 2001) may contribute to the regional tissue damage found earlier in the syndrome (Woo et al, 2003). We can now add that the flow deficits are lateralized; HF patients showed significantly lower right-sided middle cerebral artery CBFV at all but one time point during the ANS challenges relative to control subjects, and left-sided CBFV differed between HF and control subjects at all but two points of ANS testing.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Reduced CBF in HF, as demonstrated by others (Alves et al, 2005; Gruhn et al, 2001) may contribute to the regional tissue damage found earlier in the syndrome (Woo et al, 2003). We can now add that the flow deficits are lateralized; HF patients showed significantly lower right-sided middle cerebral artery CBFV at all but one time point during the ANS challenges relative to control subjects, and left-sided CBFV differed between HF and control subjects at all but two points of ANS testing.…”
Section: Discussionsupporting
confidence: 54%
“…Aberrations of vasomotor reactivity can be induced by trauma, stroke, migraine headache, or reduced CBF (Alves et al, 2005; Baumgartner & Baumgartner, 1998; Franklin, Sandström, Johansson, & Bålfors, 1997; Thie, Fuhlendorf, Spitzer, & Kunze, 1990). No participant had a history of any of these conditions, and the vasomotor reactivity differences should not result from such processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a reduction in gray matter volume is seen in areas such as the parahippocampal gyrus, cingulate gyrus, and frontal cortex (Woo, Macey, Fonarow, Hamilton, & Harper, 2003). HF patients also exhibit functional brain changes, demonstrating a 19–30% decrease in cerebral perfusion (Choi et al, 2006; Gruhn, et al, 2001), with notable reductions seen in the frontal, temporal, and parietal lobes (Alves, et al, 2005; Burra et al, 2002; Vogels, et al, 2008). In addition, there is evidence to suggest that even transient periods of reduced cerebral blood flow can have a negative effect on cognition.…”
mentioning
confidence: 99%
“…Furthermore, vast evidence links cardiac dysfunction—a significant contributor to reduced cerebral perfusion in HF [31]—with reduced cognitive test performance and abnormal neuroimaging [22,25]. HF patients have also been found to exhibit a pattern of cerebral blood flow deficits similar to those observed in patients with AD, including reduced cerebral blood flow of the pre-cuneus and posterior cingulate gyrus [32]. …”
Section: Etiology Of Cognitive Impairment In Hfmentioning
confidence: 99%